Dynamic changes of serum miR-105-3p expression and prognostic value evaluation of postoperative thyroid cancer: Dynamics of serum miR-105-3p expression - Zhou, Jianping; Song, Xiaolong; Li, Yufang; Song, Yu; Wei, Long; Yuan, Ru (Cellular and Molecular Biology, 2023)
Thyroid cancer (TC) originates from thyroid epithelial cells and is one of the common malignant tumors in the endocrine system. The aim of our study was to explore the dynamic changes of serum miR-105-3p expression after TC surgery and its correlation with clinicopathological manifestations, and evaluate its clinical value as a potential biomarker after surgery. A total of 100 TC patients were selected as the research objects. To detect serum miR-105-3p in patients and its correlation with tumor pathological characteristics and the dynamic changes of postoperative serum miR-105-3p in patients to evaluate its prognostic value as a potential biomarker. Serum miR-105-3p increases in patients with well-differentiated TC and lymph node metastasis; Serum miR-105-3p gradually decreases after surgery, and there is a significant difference between 4 days after surgery and before surgery, serum miR-105-3p level can significantly distinguish between patients with poor prognosis and good prognosis within 2 years after the operation, and it can predict the improvement of the prognosis of TC after surgery. The level of serum miR-105-3p is closely related to tumor differentiation and lymph node metastasis in TC patients. Its level gradually decreases with the passage of time after surgery. It has a good diagnostic value for the prognosis of TC after surgery and is expected to become a TC surgery. Potential biomarkers for post-diagnosis.